Application of Google Data Studio for Data Visualization at SMK Tunas Bangsa Malang - Trimono; Andreas Nugroho Sihananto; Muhammad Muharrom Al Haromainy; Edi Sugiyanto; Farkhan (Nusantara Science and Technology Proceedings, 2022)
The Department of Office Automation and Governance (OTKP) is one of the Vocational High School’s majors in Indonesia that focuses on office operations and information processing. One of the popular skill in information processing lately is data processing and visualization. In response of this trend, we propose a Google Data Studio training for Tunas Bangsa Vocational High School’s students from OTKP Majors. Google Data Studio is a free data analysis tool from Google. With this tool, users can not only display data with attractive and easy-to-understand visuals but also can process data from various sources on one worksheet. This service is mostly free, not limited to Google services such as Google Sheets but can be linked to other platforms, such as websites, applications or third party services. By the end of the training all participants have been able to use Google Data Studio for data visualization needed for offices in general.